“THE IMPACT AND FUTURE OF CONTACTLESS TECHNOLOGY AND DIGITAL PAYMENTS IN THE HOSPITALITY INDUSTRY” (CAHIERS MAGELLANES-NS, 2024)
In recent years, the hospitality industry has undergone a significant transformation with the adoption of contactless technology and digital payments. This research paper investigates the impact of these innovations on enhancing guest experiences, improving operational efficiencies, and ensuring health and safety within the sector. The study focuses on key areas where contactless technology is applied, such as mobile check-ins and check-outs, keyless room entry, and contactless dining experiences, emphasizing benefits like reduced wait times, increased convenience, and enhanced security.Additionally, the paper examines the operational advantages provided by digital payments, such as transaction efficiency, reduced cash handling, and the integration of loyalty programs, which collectively contribute to cost savings and improved guest satisfaction. Emerging trends, including block chain and crypto currency payments, are also assessed for their potential to further revolutionize financial transactions in hospitality.The research methodology includes surveys and interviews with 121 industry professionals and guests, complemented by detailed case studies, to offer comprehensive insights into the current state and future prospects of contactless technology and digital payments. The findings highlight the necessity for hospitality businesses to invest in infrastructure upgrades and staff training to fully leverage these technologies while addressing challenges related to data privacy and integration. Ultimately, this study underscores the critical role of contactless solutions in shaping a resilient and competitive hospitality industry amid a rapidly evolving digital landscape.